Ecological Neologisms and Their Semantic Features: A Comprehensive Analysis of Contemporary Environmental Terminology - Kaxramon kizi, Rakhimova Mokhinur (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
The rapid evolution of environmental science and ecological awareness has precipitated the emergence of numerous neologisms within ecological discourse. This study examines the semantic features and linguistic characteristics of ecological neologisms through a comprehensive analysis of contemporary environmental terminology. Using corpus linguistic methods and semantic field theory, we analyzed 450 ecological neologisms collected from scientific literature, environmental reports, and digital media sources between 2010-2024. Our findings reveal distinct semantic patterns including metaphorical extensions, compound formations, and hybrid constructions that reflect both scientific precision and public accessibility. The results demonstrate that ecological neologisms exhibit unique morphological structures, semantic transparency, and pragmatic functions that distinguish them from general scientific terminology. These findings contribute to our understanding of how environmental discourse shapes and is shaped by linguistic innovation, with implications for science communication and environmental education.